Tenure security solution for community-based development: A case study on communities of Jhenaidah and Gopalganj - Sharmin , Shifat Pala; Sultana, Rabeya; Tasnim, Talha; Mohammad, Afnan (Journal of Bangladesh Institute of Planners, 2023)
Bangladesh is yet to achieve tenure security for all classes of people, especially low-income communities. Since community-based development can assist in resolving this issue and implies responsibility for establishing land tenure, it has drawn a lot of attention. Community Land Trust (CLT) is one method for ensuring tenure rights in communities, and it is one of the methods used by Community Based Development (CBD). This study investigates the CBD procedure in Bangladesh and how CLT operates with regards to ownership issues. Also, this study attempts to highlight the scope for Bangladesh to use CLT in addition to examining the benefits and drawbacks of CLT. The study adopts qualitative methodologies to analyze CLT and tenure security through SWOT and comparative analysis. In the SWOT analysis, the strengths and constraints of CLT have been identified. By comparative analysis, the case studies from Bangladesh are compared with CLT based on the land tenure components. Additionally, case studies from both developed and developing countries have been conducted. After analyzing cases and the situation in Bangladesh, gaps in applied approaches were found, and several possible applications for CLT were proposed in consideration of land tenure. JBIP, Vol. 16, 2023, pp. 53-76